Association of liver fibrosis‐4 index with adverse outcomes in hypertrophic cardiomyopathy patients - Fuad A. Abdu; Redhwan M. Mareai; Lanqing Xiang; Jassur. Galip; Abdul‐Quddus Mohammed; Wen Zhang; Lu Liu; Chunyue Wang; Ayman A. Mohammed; Guoqing Yin; Xian Lv; Yawei Xu; et al. (ESC Heart Failure)
Abstract Aims The fibrosis‐4 index (FIB‐4) is a non‐invasive tool to assess fibrosis risk in chronic liver disease. We aimed to explore the relationship between the FIB‐4 index and long‐term major adverse cardiovascular events (MACE) in HCM patients. Methods and results Consecutive patients diagnosed with HCM were included. Patients were divided into two groups using a defined cutoff value established through a ROC analysis for predicting MACE (FIB‐4 ≥ 2.37 and FIB‐4 < 2.37). The final analysis comprised 187 HCM patients (34.8% females, 66.49 ± 11.43 years of age), with 47 (25.1%) in the FIB‐4 ≥ 2.37 group and 140 (74.9%) in the FIB‐4 < 2.37 group. Among these, 147 (78.6%) individuals had complete follow‐up data. Patients with FIB‐4 ≥ 2.37 demonstrated a higher prevalence of co‐morbidities such as atrial fibrillation (27.7% vs. 7.9%; P < 0.001), heart failure (55.3% vs. 24.3%; P < 0.001), elevated NT‐proBNP levels (3.03 ± 4.74 vs. 0.66 ± 1.08; P < 0.001), and lower LVEF (58.51 ± 7.86 vs. 61.84 ± 5.04; P = 0.001). Over a median of 41 (IQR 16–63) months follow‐up, MACE occurred in 49 (33.3%), with a significantly higher incidence in the FIB‐4 ≥ 2.37 group (58.8% vs. 25.7%, P < 0.001). Cardiac death rates were also elevated in the FIB‐4 ≥ 2.37 group (20.6% vs. 2.7%, P = 0.001). Cox regression analysis revealed an independent association between FIB‐4 ≥ 2.37 and a higher risk of MACE (adjusted HR: 1.919, 95% CI 1.015–3.630; P = 0.045) and cardiac death (adjusted HR: 9.518, 95% CI 1.718–52.732; P = 0.010). Furthermore, the FIB‐4 index shows positive correlations with left atrium diameter (r = 0.229; P = 0.003), septal thickness (r = 0.231; P = 0.002), posterior wall thickness (r = 0.235; P = 0.001), and NT‐proBNP (r = 0.271; P < 0.001). Conversely, a negative correlation was observed between the FIB‐4 index and left ventricular ejection fraction (r = −0.185; P = 0.011). Conclusion Elevated FIB‐4 index, indicative of liver fibrosis, is independently associated with an increased risk of long‐term MACE in HCM patients. This emphasizes the potential influence of liver function abnormalities on HCM prognosis, underscoring the need for comprehensive risk assessment in clinical management.